Garfield fat cat 3-pack. Volume 23 - Davis, Jim, 1945 July 28- (Garfield fat Cat 3-pack, 2021)
"Garfield slurps and burps: Who has time for manners when there's food to be inhaled? Garfield eschews etiquette in favor of binging and belching. And who can blame him? He's only human! So get rude 'n' crude and pig out on this collection of tasty comics"--Publisher marketing